The hero: Charles A. Lindbergh and the American dream - Davis, Kenneth S. frey50 (Doubleday and Company, Inc. Garden City, New York, 1959)
Here is a veritable torrent of a book exciting, suspensful, ranging from comic absurdity to tragic irony through a hundred dramatic episodes while presenting a whole gallery of fully realized, widely various characters.
Keywords: Lindbergh, Charles A. -- 1902-1974; Air pilots -- Biography. -- United States